Biomedical Optics Express Feature Issue Introduction: Optical Manipulation and Its Applications (OMA) 2023 - Jones, Philip; Bernatová, Silvie; Kotsifaki, Domna G (Biomedical optics express, 2024)
The feature issue of Biomedical Optics Express presents studies that were the focus of the Optical Manipulation and its Applications (OMA) meeting that was held on 24 - 27 April 2022 in Vancouver, Canada.